IMF Staff papers : Volume 3 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1953)
This IMF staff paper provides an analysis of the factors affecting reserve adequacy. Adequacy of reserves depends on the prospective problems that confront a country and, therefore, differs from country to country and from problem to problem. An adequate reserve position permits both the monetary authorities and the private traders of a country to look ahead and to plan their affairs with confidence. When reserves are inadequate, a country's foreign trade may be subject to sudden starts and stops, as restrictions are imposed or relaxed, or its exchange rate may fluctuate sharply. The essentially defensive character of supplementary reserves obtained with firm assurances of repayment in the short-term or medium-term future has already been pointed out. Defensive measures are important, however; and, in order to prevent small depressions from growing into large ones, such supplementary reserves should be supplied early, on liberal terms, and in adequate amounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet